HLA Typing in Iraqi Patients with Obesity and Primary Osteoarthritis. - Al-Mukhtar, Sadiq Abbas; Abdul-Kareem, Faris; Zalzala, Haider Hashim; Mahdi, Batool Mutar; Raouf, Hyam; Abid, Laheeb Ali; Nehad, Zena (AL-Kindy College Medical Journal, 2013)
Background: Osteoarthritis (OA) is a degenerative joint disease. It is one of the major causes of disability in developed and developing countries. Human leukocyte antigen (HLA) as part of immune system has a role in the disease process.Objectives: To investigate whether there is an association between HLA class II-DRB and OA.Methods: A case control study with 26 patients with osteoarthritis and 22 apparently healthy obese control persons matching in ethnicity were enrolled in this study during the period between October 2012 till March 2013. Direct interview was done with each patient and HLA typing was done by molecular method using Sequence Specific Primer (PCR-SSP) method using One Lambda Kit-USA. Results: The results showed that females were more affected than males with disease when compared with control. Odds ratio were used to test level of significance. This study showed that HLA DR4 (DRB1*04), DR2 (DRB1*15 and DRB1*16), DR9 (DRB1*09), DR10 (DRB1*10, DRB5*, DRB4* and DRB3*) (odds ratio: 14.26, 9, 9, 9, 14.26, 9.5 and 4.5) respectively are associated with OA.Conclusions: OA is highly associated with HLA class II DR4 (DRB1*04), DR2 (DRB1*15, DRB1*16), DR9 (DRB1*09), and DR10 (DRB1*10).DR5 (DRB1*05) is not associated with OA.